Estudos Integrados do Fundo Marinho da Baía da Ilha Grande, RJ - Belo, Wellington Cecccopieri (2001)
Based on high-resolution seismic data (sub-bottom profiler 7,0 kHz and side scan sonar 100 kHz) and geological bottom samples, three aspects of the Ilha Grande Bay seabed were investigated: cofacies, bedforms and potential risk attributes. Their resultswere integrated on a digital-bathymetric map of the region. The seabed along the eastern central channel of the bay was characterized by eight bottom sedimentary patterns. Such patterns showed variations in the texture, in the bio-debris content and in the acoustic back-scattering of the sediments. Among these patterns, lithobioclastic muds are closer to the land, terrigenous muds are closer to Ilha Grande and sands are far eastward from the central channel. Observed evidences of modern facies transitions from sub-environments dominated by higher energy agents (waves) to facies dominated by lower energy agents (tides, bottom currents) were related to the complex submarine topography and to the coast line orientation. The boundary geometry among the ecofacies also suggests a hydrodynamic control by wave action and bottom currents. Evidences of these combined effects of waves and currents were approached based on the observed bedforms. Such sedimentary structures are predominantly "mega ripples" located in depths around 16 m, nearby Conceição de Jacareí. There is a textural transition of the bottom sedimentary patterns from westward to eastward. Their crests are NE-SW and ESE-WNW oriented and plenty variable in the form (straight line, wavy, forked, discontinuous). Their heights ranged from 0.2 to 0.55 m with medium value around 0.35 m. Based on the bedform parameters (wavelength and height) and by using diagrams relating the medium diameter of the grains, to the depth and to the type of the structure, the speed of the flow up to 1,0 meter from the bottom (U100) was estimated. It varied from 46 cm/s (medium sands) to 34 cm/s (very fine sands) - from eastward to westward. The medium speed of the stationary flow (U), differently, varied from 54 cm/s to 64 cm/s, respectively. The Froude number range (F) (0.026-0.051) indicated a relatively calm regime of the generating flow. Four studies concerning to wave action indicated that highenergy waves usually observed in the area can contribute to the genesis of the observed bedforms being a good evidence that they could be active. Besides, they could be subject to changes on their geometry along the year. The bottom in this area would be mobile during these events with speed of the oscillatory flows around 50 cm/s. Upon sporadic events of higher energy (~ 80 cm/s), mainly in the winter, there would be larger readiness of sediment for the bottom transport by currents. Therefore, all these observed vii characteristics of the eastern-central channel seabed of the bay indicate that waves and currents may act on the sediments sorting by an interplay to the geometry of the bay characterizing different bottom types. The resulting oscillations on the level of energy also can contribute to the bedforms generation, based on sporadic higher energy events. The heterogeneous seabed with transitions among bottom sedimentary patterns and sites of mobile bedforms are features that represent potential risks to the operational activities of the oil industry. Among others seabed features observed in the seismic records, they were classified in two potential risk attributes: structural and sedimentary. Finally, as a qualitative result of the accomplished studies, it was observed three areas where there was a juxtaposition of the potential risk attributes: in the surrounds of Estrelas sound, in an area between Itapinhocanga and Conceição de Jacareí sounds and in the coastal depression (canal central).